Augmented Reality Learning Media for Enhancing Elementary Students’ Conceptual Understanding - Putri Nur Sakina Karadjo; Herlina Herlina; Sisriawan Lapasere; Mahfud M. Gamar; Sri Wahyuni (CV. Dharma Samakta Edukhatulistiwa, 2026)
This study aims to examine the development process, validity, and practicality of Augmented Reality-based learning media in enhancing fifth-grade students’ understanding of science concepts at SDN Inti Dolago on the topic “Seeing Because of Light.” Issues in science education indicate that students still struggle to grasp abstract concepts because instruction is dominated by lecture-based methods and the limited use of visual media. This study employed the Research and Development (R&D) method using the ADDIE model, implemented through the implementation stage. The research subjects consisted of 20 students, a classroom teacher, and two expert validators. Data were collected via expert validation sheets and user response questionnaires, analyzed using percentage techniques based on a Likert scale to determine the media’s validity and practicality levels. The novelty of this study lies in the development of Assemblr Edu-based Augmented Reality media on visual system material in elementary schools to support conceptual understanding through interactive three-dimensional object visualization.The results showed that the media received a validity score of 82.50% from subject matter experts and 84.00% from media experts, as well as positive responses from teachers and students, making it feasible and practical for use in IPAS learning.